Aquatic Invertebrate Fauna of Song Thanh Nature Reserve in Quang Nam Province, Vietnam - Ngo Xuan, Nam; Trung, Nguyen Thanh (VNU Journal of Science: Natural Sciences and Technology, 2017)
The study analyzed the composition of the aquatic invertebrate fauna of Song Thanh Nature Reserve in Quang Nam province of Vietnam. There were 48 qualitatively and 48 qualitative samples were collected at 12 sitesby plankton net for the zooplankton (plankton net No 52 for qualitative samples and plankton net No 57 for quantative samples), but with zoobenthos, using PondNet for the qualitative samples and Subber Net (50 cm x 50 cm, mesh size 0,2mm) for quantative samples. This investigation was realized in March and September 2015. As a result, a total of 166 species belonging to two groups, the zooplankton group has 12 species, 11 genera, 9 families, 3 ordes, 2 classes and the zoobenthos group has 154 species, 120 genera, 59 families, 13 orders,4classes. The most richness class is insecta with 141 species, 109 genera, 52 families, 9 orders. Moreover, pH is the environmental parameter that has more effective than others on zoobenthos group both in dry and rainy seasons; whereas, turbidity and total dissolved solids are two factors that effectmore strongly than others on zooplankton group. The number of zooplankton species in dry season is lower than in rainy season and in contrast with zoobenthos species. The species of Crustacea and Bivalvia classes are invisible in the dry season, they only appear the species that belong to insecta and Gastropoda classes.             Keyword : aquatic invertebrate, fauna , Song Thanh , Nature Reserve , Vietnam